1983
DOI: 10.1111/j.1752-0606.1983.tb01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Acceptability of Alternative Marital Therapies: A Comparative Analysis

Abstract: Client acceptability of treatment procedures has recently become a significant concern in the assessment of psychotherapeutic effectiveness (Kazdin, French & Sherick, 1981; Wolf, 1978). Formally, acceptability refers to the fairness, appropriateness and intrusiveness of the treatment procedure as judged by clients, lay persons and nonprofessionals (Kazdin, 1980a). Unfortunately, marital and family therapists have yet to utilize this criterion in an evaluation of their psychotherapeutic interventions. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Acceptability of a particular treatment approach has been recognized as an important variable in the assessment of treatment effectiveness ( Bornstein et al, 1983; 1987; Flammang & Wilson, in press; Kazdin, 1980a; b; Kazdin, 1981; Kazdin, French & Sherick, 1981; Wilson & Flammang, 1990; Wilson, Flammang & Dehle, in press; Wilson & Wilson, 1991; Wolf, 1978) and may represent an important patient characteristic in outcome studies (Wilson, 1990). As defined by Kazdin (1980a), "acceptability refers to the judgments about the treatment procedures by nonprofessionals, lay persons, clients, and other potential consumers of treatment" (p. 259).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acceptability of a particular treatment approach has been recognized as an important variable in the assessment of treatment effectiveness ( Bornstein et al, 1983; 1987; Flammang & Wilson, in press; Kazdin, 1980a; b; Kazdin, 1981; Kazdin, French & Sherick, 1981; Wilson & Flammang, 1990; Wilson, Flammang & Dehle, in press; Wilson & Wilson, 1991; Wolf, 1978) and may represent an important patient characteristic in outcome studies (Wilson, 1990). As defined by Kazdin (1980a), "acceptability refers to the judgments about the treatment procedures by nonprofessionals, lay persons, clients, and other potential consumers of treatment" (p. 259).…”
mentioning
confidence: 99%
“…Originally applied to the treatment of behavioral disorders in children ( Kazdin, 1980 a , b ), evaluation of treatments in terms of acceptability has been recently applied to alternative sex therapies (Wilson & Wilson, 1991) and marital therapy formats (Flammang & Wilson, in press; Wilson & Flammang, 1990; Wilson, Flammang & Dehle, in press). Empirical studies have demonstrated that differentiation of treatment options through ratings of acceptability is easily achieved by student populations (Kazdin, 1980a, b; Bornstein et al, 1983), inpatient children, parents, and hospital staff (Kazdin et al, 1981). Published research to date, however, has focused exclusively on the treatment of childhood disorders, sexual dysfunction, and marital therapy.…”
mentioning
confidence: 99%
“…in-depth insight is the only true path to change that will be sufficiently internalized to endure over time and changing circumstance, established methods of ateach partner's position.) Indeed, time requirements alone have greatly hampered the development of effective shorter-term dynamic models for individual interfind behavioral and systems approaches "more acceptable' than strictly analytic ones (Bornstein et al, 1983).…”
Section: Background and Literaturementioning
confidence: 99%
“…Indeed, time requirements alone have greatly hampered the development of effective shorter-term dynamic models for individual intervention, much less models involving multiple individuals. With such difficulties inherent in translating individual technique to couples settings, it is hardly surprising that there are findings reported in the literature to trie effect that patients find behavioral and systems approaches "more acceptable' than strictly analytic ones (Bornstein et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, though, acceptability research has been extended to many other areas of psychological treatment. For example, treatments for agoraphobia (Aronson, Craig, Thomason, & Logue, 1987;Norton, Allen, & Walker, 1985), depression (Banken & Wilson, 1992;Hall & Robertson, 1998;Rokke, Carter, Rehm, & Veltrum, 1990;Tarnowski, Simonian, Bekeny, & Park, 1992), developmental disabilities (Epps, Prescott, & Horner, 1990), eating disorders (Newton, Hartley, & Sturmey, 1993;Sturmey, 1992), geriatric behavior problems (Lundervold, Lewin, & Bourland, 1990;Lundervold et al, 1991), marital therapy (Bornstein et al, 1983;Bornstein et al, 1987;Upton & Jensen, 1991;Wilson & Flammang, 1990;Wilson, Flammang, & Dehle, 1992), mental retardation (Rasnake et al, 1993;Tarnowski et al, 1989), panic disorder (Aronson et al, 1987;Hecker, Fink, & Fritzler, 1993), paradoxical interventions (Betts & Remer, 1993;Cavell, Frentz, & Kelley, 1986a, 1986bHunsley, 1993;Hunsley & Lefebvre, 1991), pediatric behavior problems (Tarnowski et al, 1987), sex offenders (Lundervold & Young, 1992), sex therapy (Wilson & Wilson, 1991), and sport psychology (Brewer et al, 1994;Jensen, 1997;Jensen et al, 1992;Maniar et al, 2001) have all been evaluated with regard to acceptability.…”
Section: Research On Acceptabilitymentioning
confidence: 99%